DE L’HÉRITAGE DANS LE RÉCIT DE FILIATION AU MASCULIN - Carmen ANDREI (Studia Universitatis Babeş-Bolyai. Philologia, 2018)
On Heritage in the Filiation Narrative in the Male Gender. My article analyses a testimony of the return to origins published in 2009 by a famous voice in the contemporary Canadian French literature: Dany Laferrière, L’énigme du retour. The novel is built on the double geographical and mental route past-present, present-past, between the country of origin and the adoptive countries (Quebec and the United States), on activating individual and collective memory, on a favorite topos of the postmodern climate, viz. identity interrogation. It is complex, necessary to gaining wisdom. Once understood, accepted, assumed, it is no way perceived as heart-wrenching or vindictive, but instead it helps the author regain peace and evolve. The exile means liberation and return, identity loss and regain. This is a complex autobiography, with the most intimate writing of intimacy, an archeological inquiry collecting bribes/remnants of a troubled past. For Dany Laferrière, the direct paternal affiliation is sublimated, it fails, the heritage is taken over by a spiritual father and it aims at being relegated to the grandson.